Hubungan Pengetahuan Tentang Tanda Bahaya Dalam Kehamilan Dengan Keteraturan Antenatal Care Di Puskesmas Batua Kecamatan Manggala Kota Makassar - Kasmawati Kasmawati; Jumrana Jumrana (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
The aim of this research is to determine the relationship between knowledge about danger signs in pregnancy and the regularity of Antenatal Care at the Batua Community Health Center, Manggala District. The research design used in this study is observational with a